Clinical Correlates of Awareness for Balance, Function, and Memory: Evidence for the Modality Specificity of Awareness - Megan E. O'Connell; Vanina Dal Bello-Haas; Margaret Crossley; Debra Morgan (Journal of Aging Research)
Awareness in dementia is increasingly recognized not only as multifactorial, but also as domain specific. We demonstrate differential clinical correlates for awareness of daily function, awareness of memory, and the novel exploration of awareness of balance. Awareness of function was higher for participants with mild cognitive impairment (aMCI and non-aMCI) than for those with dementia (due to Alzheimer disease; AD and non-AD), whereas awareness of memory was higher for both non-aMCI and non-AD dementia patients than for those with aMCI or AD. Balance awareness did not differ based on diagnostic subgroup. Awareness of function was associated with instrumental activities of daily living and caregiver burden. In contrast, awareness of balance was associated with fall history, balance confidence, and instrumental activities of daily living. Clinical correlates of awareness of memory depended on diagnostic group: associations held with neuropsychological variables for non-AD dementia, but for patients with AD dementia, depression and instrumental activities of daily living were clinical correlates of memory awareness. Together, these data provide support for the hypothesis that awareness and dementia are not unitary and are, instead, modality specific.